Highly-oriented (104) polycrystalline α-Al2O3 transparent ceramics prepared by a templated grain growth method. Issue 4 (April 2019) - Yang, Qinghua; Wang, Huanping; Chen, Shuilin; Zhang, Long; Xu, Shiqing
Abstract: Highly-oriented (104) polycrystalline α-Al2 O3 transparent ceramics were prepared by a templated grain growth (TGG) method using A-plane single-crystal sapphire as the template. This is the first report, to best of our knowledge, on polycrystalline α-Al2 O3 ceramics oriented to non-optical axes. XRD and SEM results indicate that samples with high oriented grains and high-density structure are prepared. Compared to random samples, the oriented samples exhibited an increase in the real in-line transmittance (at 650 nm) from ∼23% to ∼62%. Moreover, the transmission remains a high level as the wavelength shifts toward the UV range (< 300 nm). This method can be extended to other uniaxial materials without optical axes in order to produce polycrystalline ceramics with excellent optical transparency.